Moisture Use Efficiency of Dryland Crops as Influenced by Fertiliser Use IV. Grain Legumes - Singh, R p; Ramakrishna, Y S (Annals of Arid Zone, 2016)
Studies carried out on the response of various grain legumes to fertiliser use under rainfed conditions both at I. A. R.I., New Delhi and C. A. Z. R. I., Jodhpur showed that under Delhi conditions pigeon pea exhibited the highest moisture use efficiency (2.81 kg/mm/ha) followed by mung beans (2.34 kg/ mm/ha) and soybean ( 2.24 kg/mm/ha). Soybean and chick peas had responded to lower doses of fertiliser (40 kg P20s/ha) and to the placement method of fertiliser application, while mung beans and pigeon pea responded to higher levels of fertiliser (80 kg P20s/ha), the broadcasting method proving as efficaceous as other methods tried. At Jodhpur mung beans, moth beans and cluster beans had exhibited higher moisture use efficiency and had responded well to fertiliser application.